2022
DOI: 10.2147/dmso.s366609
|View full text |Cite
|
Sign up to set email alerts
|

ViphyllinTM, a Standardized Black Pepper Extract Exerts Antihyperglycemic Effect and Improves Sciatic Nerve Conduction in High Fat Diet/Streptozotocin-Induced Diabetic Model Rats

Abstract: Purpose Research on plant-based formulations has drawn considerable attention in the management of diabetic neuropathy (DN) for having lesser side effects than the synthetic counterparts. Here, we have investigated for the first time the therapeutic effects of a standardized Piper nigrum L., (black pepper) seed extract, Viphyllin TM in mitigating hyperglycemia and neuropathic pain of type 2 diabetes model rats. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Bangalore, India, prepared from that contains not less than 30% of -caryophyllene (BCP) that exerts oral hypoglycaemic activity. Studies were conducted on diabetic rats, and it was found to exert antidiabetic effects and improve nerve conduction to mitigate neuropathic pain 41 . It is a cannabinoid receptor 2 (CB2) agonist with potential pharmacological actions such as dyslipedemia and hyperglycemia.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Bangalore, India, prepared from that contains not less than 30% of -caryophyllene (BCP) that exerts oral hypoglycaemic activity. Studies were conducted on diabetic rats, and it was found to exert antidiabetic effects and improve nerve conduction to mitigate neuropathic pain 41 . It is a cannabinoid receptor 2 (CB2) agonist with potential pharmacological actions such as dyslipedemia and hyperglycemia.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%